IMMU-18. MIGRATION OF DENDRITIC CELLS THROUGH THE BRAIN-MENINGEAL LYMPHATIC-DRAINING LYMPH NODE NETWORK IN ORTHOTOPIC GLIOMA MODELS. (14th November 2022) - Batich, Kristen; Chen, Ching Wen; Wellford, Sebastian; Dao, Kianna; Moseman, Annie Park; Hotchkiss, Kelly; Cook, Sarah; Snyder, David; Sampson, John; Moseman, Ashley
Abstract: INTRODUCTION: Limited migration of dendritic cell (DC) vaccines to draining lymph nodes (DLN) remains a major limitation to DC efficacy for malignant gliomas. Our prior work demonstrated that increased peripheral DC migration to DLN results in enhanced antitumor efficacy. Given this, we studied DC trafficking in mouse gliomas, the meningeal lymphatic vessel (MLV) system, and the draining cervical lymph nodes (CLN). METHODS: To elevate host DC populations, C57BL/6 and VMDk mice were implanted with B16-FMS-like tyrosine kinase 3 ligand (FLT3L) melanoma or with B16-FLT3L supernatant. Mice were implanted intracranially with CT2A, GL261-OVA, and SMA560 syngeneic glioma lines in the right parietal lobe. Antitumor efficacy was measured by tumor weights and median overall survival (mOS). RESULTS: DC injected into glioma hemispheres display delayed kinetics of peak migration to CLN compared to control (7 days (d) vs 3d post-injection (pi), respectively). Migration of intraventricular (ivn)-injected DC to CLN is superior at days 1, 3 and 7 pi when glioma is present (p = 0.026). B16-FLT3L supernatant results in a disproportionate systemic expansion in conventional type 1 over type 2 DC (cDC1 > cDC2) compared to media control (cDC1, cDC2 fold change over media for spleen = 27, 11; DLN = 6, 2; blood = 6, 3). Pulsed dosing of FLT3L supernatant results in significantly greater numbers of splenic cDC1 compared to daily FLT3L dosing (p = 0.002). Mice with CT2A and continuous FLT3L secretion in vivo show longer survival (mOS 30d) compared to mice with continuous GM-CSF secretion (mOS 22d) (p = 0.009). Mice with SMA560 and FLT3L secretion have significantly reduced glioma growth compared to tumor alone, GM-CSF-secreting tumors, and mixed FLT3L/GM-CSF-secreting tumors (p = 0.029). CONCLUSION: FLT3L signaling in vivo results in cDC1 > cDC2 generation and migration through the CNS with more favorable glioma efficacy. Modeling of DC migration through the glioma-MLV-CLN system with FLT3L stimulation permits testing of strategies to improve DC therapy.